Supplementation of calcium, magnesium, phosphate, and potassium in critically ill patients: A multicenter cohort study - Christopher J. Yarnell; Thomas Bodley; Anica C. Law; George Tomlinson; Emily A. Vail; Nicholas A. Bosch (PLoS ONE, 2026)
Objective To investigate hospital-level variation in the supplementation of calcium, magnesium, phosphate, and potassium in critically ill patients. Design Retrospective cohort study. Setting Premier Healthcare Database of inpatients from the USA. Patients Adults (age ≥ 18 years) admitted to an intensive care unit (ICU) on hospital day 1 between October 1, 2022 and July 31, 2024, who had at least one calcium (total or ionized), magnesium, phosphate, or potassium level measured in an ICU between day 2 and 28. We excluded patients with renal failure, a pregnancy-related diagnosis, and intracranial bleeding on admission. Interventions Calcium, magnesium, phosphate, or potassium supplementation. Measurements and main results We included 47,988 patients from 67 ICUs across 52 hospitals, totaling 167,621 patient-days with a measurement of one of the studied electrolytes. Median age was 64 years (interquartile range [IQR] 52–74) and 46% (22,057) were female. There were 38,621 patients (80.5%) with a minimum value below a lower limit of normal, and 33,626 (70.1%) patients who received supplementation. Across hospitals, the median (IQR) percentages receiving supplementation per day were: calcium 9.4% (6.7–12.2); magnesium 28.6% (22.6–35.0); phosphate 19.1% (15.9–23.2); potassium 28.9% (25.8–34.6). From a multilevel model, the median relative odds of supplementation, comparing any two hospitals, ranged from 1.51 (95% confidence interval [CI] 1.48–1.55) for potassium to 2.09 (95% CI 1.99–2.19) for magnesium. At most hospitals, there were no calcium or phosphate levels at which the percentage receiving supplementation exceeded 50%. At 75% of hospitals there was a magnesium level at which the percentage receiving magnesium supplementation was 50% or more (range: 1.5–2.1 mg/dL), and at 96% of hospitals there was an analogous potassium level (range: 3.3–3.9 mmol/L). Conclusion Supplementation of calcium, magnesium, phosphate, or potassium is common in critically ill patients and varies across hospitals, suggesting a need for randomized trials to clarify optimal supplementation practices.